Long-term performance of politically connected winning firms after 2014 indonesian presidential election - Akbar Grady Serano, Dillon; Anny Nainggolan, Yunieta (Journal of Business and Management, 2019)
This research discuss whether there is a difference between the long-term value of firms that is politically connected to president Jokowi and firms that is politically connected to runner up president Prabowo after Indonesian presidential election in year 2014. This research aims to investigate (1) long-term value of politically connected firms after 2014 election, (2) long-term value of politically connected winning and losing firms after 2014 election, and (3) whether politically connected winning firms have higher long-term value than politically connected losing firms. This research collect 52 politically connected firm’s data that is connected to the winning and losing side from year 2014 to 2019. The result of this study is that there is a difference between the long-term values of firms that is politically connected to the winning side compared to firms that is politically connected to the losing side. The result of the event study that has been done is to come to the conclusion that politically connected winning firms (PCWs) result in an average abnormal return of -37% compared to politically connected losing firms that result in an average abnormal return of -84%. This finding can also be seen through ABHAR testing, for the total difference in the research period is 47% and is statistically significant in a 1% level. Lastly, this result can provide a guideline for investors that it is more profitable to invest long-term in politically unconnected firms after a presidential election. KEYWORDS: Firms Long Term Performance, Indonesia, Political Connection, Presidential Election.